Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

L'intolérance: une problématique générale - Noël, Lise (Boréal, 1989)
Tableau d'ensemble qui montre comment s'articulent les rapports dominants/dominés autour de paramèties tels que le sexe, l'âge, la condition mentale, la langue, etc.
Keywords: 1900-1999; approches et analyses; cours; intersectionnalité; lit3495; premier cycle; périodes historiques; racisme; sexisme; soc2014; systèmes d'oppressions; thématiques; violences

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

Polity and Group Difference: A Critique of the Ideal of Universal Citizenship - Young, Iris Marion (Ethics, 1989)
Keywords: approches et analyses; cours; discipline; droits civiques; histoire et politique; intersectionnalité; justice sociale; philosophie politique; pol4212; premier cycle; science politique; science politique et droit; sciences humaines; thématiques

White privilege and male privilege: A personal account of coming to see correspondences through work in women's studies - McIntosh, Peggy (Wellesley College, Center for Research on Women, 1988)
Through work to bring materials and perspectives from Women's Studies into the rest of the curriculum, I have often noticed men's unwillingness to grant that they are overprivileged in the curriculum, even though they may grant that women are disadvantaged. Denials that amount to taboos surround the subject of advantages that men gain from women's disadvantages. These denials protect male privilege from being fully recognized, acknowledged, lessened, or ended.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discours dominant; intersectionnalité; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; savoir expérientiel; sexisme; systèmes d'oppressions; états-unis

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Popular culture critical readers, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. --back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Learning from the outsider within: The sociological significance of black feminist thought - Hill Collins, Patricia (Social Problems, 1986)
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; intersectionnalité; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; épistémologie; états-unis

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Black women: Shaping feminist theory - hooks, bell (Feminist theory: From margin to center, 1984)
Keywords: 1900-1999; EDI; amériques; approches et analyses; cours; fem1000; intersectionnalité; justice sociale; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

Not in our genes: biology, ideology, and human nature - Lewontin, Richard C.; Rose, Steven P. R.; Kamin, Leon J. (Pantheon Books, 1984)
Keywords: approches et analyses; biologie; corps; cours; discipline; génétique; intersectionnalité; justice sociale; lit4700; premier cycle; racisme; santé; sciences; sexisme; systèmes d'oppressions; thématiques

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Powers of desire the politics of sexuality - Snitow, Ann Barr; Stansell, Christine; Thompson, Sharon (New feminist library, 1983)
This provocative anthology brings together a diverse group of well-known feminist and gay writers, historians, and activists. They are concerned not only with current sexual issues-abortion, pornography, reproductive and gay rights-but they also raise a host of new issues and questions: How, and in what ways, is sexuality political? Is the struggle for sexual freedom a complement to other struggles for liberation, or will it detract from them? Has the sexual revolution diminished or enriched the lives of women?
Keywords: approches et analyses; cours; discipline; histoire; intersectionnalité; justice sociale; lesbianisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; thématiques; études féministes

Visions partielles, visions partiales: visions des minoritaiers en sociologies - JUTEAU-LEE, Danielle (Sociologie et sociétés, 1981)
Résumé L'irruption du discours des minoritaires en sociologie fait éclater le discours des majoritaires en provoquant la remise en question de leurs explications à tendance naturaliste, culturaliste et psychologisante. Affichant le caractère partiel et partial de leurs visions, les femmes et les "ethniques" favorisent l'éclosion de synthèses provisoires, susceptibles de rendre compte des formes multiples de l'oppression
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; patriarcat; point de vue situé; pol4212; premier cycle; racisme; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; universalisme